Hukum Pelestarian Terumbu Karang sebagai Penyangga Produktivitas Perikanan - Lena Farsia; Wardah Wardah (Kanun Jurnal Ilmu Hukum, 2014)
There is the fact that in Aceh, more than 60 percent of coral reef are bleaching. Scientiests also found that 80 percent of marine species in Aceh marine are going to death. It is a dangerous situation because coral reef are a protecting place for fish and other sea biotas. Huge fishes are also usually gathering around the coral reef that provide food for them. This research will be conducted at the coral reef ecosystem in Ujung Pancu, Kecamatan Peukan Bada, Great Aceh. The aims of the research are to analyze the rule of protecting coral reef in Aceh Province, to explain the efforts of coral reef protection in Ujong Pancu area in order to increase the fishing productivity, and to comprehend the challenges faced in preserving coral reef in Ujong Pancu area. The research shows that the legal basis for the coral reef conservation has regulated both in national and local law. It means that the government has been taking into account and giving proper attention to the conservation program. Moreover, the coral reef conservation in Ujung Pancu also got supports not only form the local government but also from the civitas academica but also from the local and international  non governmental organizations. It is concluded that the barriers in coral reef preserving program in Ujung Pancu are minimalized.  The Potential of Coral Reef of Law as Fishery Productivity Buffer